Pengaruh Macam Pupuk Organik Terhadap Pertumbuhan dan Hasil Jagung Manis (Zea mays-saccharata, Start) - Dewi, Sukuriyati Susilo; Isnawan, Bambang Heri; Purwana, Dwi (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2005)
A field research to observe the effect of kinds of organic manure and on growth  and yield of sweet  corn  was  done  in Danguran   village,  Klaten  Regency  of Midle Java. The research was conducted during August to October 2003. The field experiment was arranged in a Randomized Complete Block Design, with 3 replications. The kinds of organic manure treatment consisted of 5 levels which are: no farm manure (PKO), chicken farm manure (PKl), vermicompost or Kascing (PK2), cow farm manure A (PK3), and cow farm  manure-B (PK4). Each organic matter given was 10 ton /ha. The result showed that the chicken farm manure gave the significantly higher growth and yield  of sweet  corn  than  the others.  The average sweet corn yield obtained in this research was 16,2 ton/ha.